Global Imbalances and Bank Risk-Taking - Daniel Marcel te Kaat; Valeriya Dinger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Financial crises are usually preceded by large current account deficits. However, the channel through which international capital flows affect financial stability is hardly identified, yet. In this paper, we study the impact of current account balances on bank risk-taking making use of the exogenous and huge variation in capital flows within the euro area between the years 2001 and 2012. We find that bank risk-taking is positively associated with current account deficits. We provide a series of tests showing that this is the case both because banks in countries with large external deficits substitute new investments in asset markets (e.g. sovereign debt) with loans that are typically riskier and because the average quality of bank loans deteriorates.
Keywords: F32; F41; G01; 330